Resource Struggle, Resultant Realities and the Future of Maragoli Land Use - Muhandale, Alex Amisi (Journal of Agricultural Policy, 2020)
Land has remained one of the most basic and valuable economic resource right from the pre-colonial to the post independent Kenyan society. The success or failure of every society is always pegged on how prudent the society manages the resources within its reach in the midst of changes, challenges and opportunities that time and space avails every single moment. Being part of the Kenyan society, the Maragoli community has never been left out of the land question that has troubled Kenya over time. The pre-colonial Maragoli society had a land tenure system which was characterized by communal control of land together with its resources and practiced individual land ownership. Though land was communally owned at the general level, it was individually owned and tilled at the family level. The basis of land administration was the customary law executed by the elders who had the overall powers over the production resource. Through colonial policies such as alienation of the Africans' land, confiscation of livestock, introduction of taxes and the cash economy; all these mechanisms brought about disequilibrium in the Maragoli pre-colonial land use. With this in mind therefore, this paper examined the nature and realities in resource struggle and the future of such struggles especially in regard to land use in the post-independence Kenya, using the case of the Maragoli. Through the articulation theory, this paper demonstrates that the interaction between the pre-colonial Maragoli land use practices and the colonial land policies greatly impacted on the Maragoli socio-economic and political structures. Due to the cash crop economy, the traditional Maragoli communal attitudes towards land as a resource are fading out resulting into individual emphasis on land use. This individual emphasis on land use is the major cause of uneconomical subdivision of land, insecurity and increased poverty. It is from the above perspective that the paper analyses the post-independence Maragoli land situation, some of the key causes of uneconomical subdivision of land and the possible solutions.